The effectiveness of a parent-implemented, phonological awareness programme on the phonological awareness skills of preschool children - Bennett H; Denston A; Arrow A (Springer Nature, 2023)
A child’s early literacy and language skills are the most reliable predictor of future academic achievement. Despite vast amounts of research supporting this link, many children start formal schooling with low early literacy skills. Without intervention or support, these children will likely continue to fall behind their peers. This exploratory study investigated the effectiveness of a parent-led phonological awareness programme (n = 3), implemented at home with their 4-year-old children (n = 4) in Christchurch, New Zealand. This study used an exploratory case study mixed methods design. The programme focused on improving children’s phonological awareness skills by providing parents with readily available activities which taught a range of phonological skills. Parents were supported throughout implementation by the researcher with coaching and modelling. Overall, the study found parents to be effective at implementing the phonological awareness programme and facilitating the development of their children’s emergent literacy skills. Children demonstrated increased phoneme identification, blending and segmenting skills and additional skills not explicitly taught, such as phoneme manipulation. Participation in the programme also positively affected children’s interest in literacy activities, such as reading and writing. Parent reports identified positive effects on children’s articulation, speech, engagement and overall confidence. Parents were positively affected by their participation in the programme, with reports of increased confidence in their English proficiencies and literacy skill development.
Keywords: Early literacy; Phonological awareness; Emergent literacy skills; Parent implemented